THE JANISSARIES OF THE 20th CENTURY: MOHSIN HAMID’S NOVEL RELUCTANT FUNDAMENTALIST - Shymchyshyn, Mariya (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.147 The article deals with Mohsin Hamid’s novel “The Reluctant Fundamentalist” (2008), a reflection on the events of 9/11 in New York. The 9/11 terrorist attack influenced not only the US but the whole world community. Unlike TV reporters, journalists, and photographers, writers were disoriented in finding words and forms after the fall. It took them time to reconsider the event and choose narrative strategies for presenting their versions of the tragedy. The novels about 9/11 are neither the justification of what had happened nor the explanation of it. The writers try to reflect on the nature of the world today, the existential crisis, the reasons for overwhelming aggression and hate that dominate relationships between people of different skin colors or religious believes. Ambiguity as the immanent feature of postmodernist writings beseems for the description of a perplexed condition after the tragedy. The novel “The Reluctant Fundamentalist” is a monologue of a young Pakistani told to an American stranger in a café in Lahore. Born in Pakistan, educated at Princeton, and the best former employee in a New York firm “Underwood Samson”, that “focuses on the fundamentals”, Changez quietly discloses his revelation after 9/11. On the one hand, the narrative reminds a confession as the listener is silently listening, and readers know about his reactions from the protagonist’s remarks. But there is no penitence in his confession. On the other hand, it is the explanation from Muslims who were silenced and blamed as terrorists and fundamentalists. It is also a deconstruction of the dominant American official discourse of the 9/11 attack. The novel is a counternarrative to stereotypes of Islam and Muslims. Step by step Changez discloses that US political and economic power, gained by the dispossession of weaker nations and states, contributed to the 9/11 events. The author of the article draws parallels between the novel and recent scholarship on new imperialism and the global economy. In particular, works by Michael Hardt and Antonio Negri “Empire” and “Multitudes: War and Democracy in the Age of Empire”. They argue that the modern type of militarist empire disappeared and a new empire which is a blend of technology, economics, and globalization emerged. The primary symptom of the coming of Empire is the declining sovereignty of nation-states and their inability to regulate economic and cultural exchange. The next point is that the new Empire does not rely on fixed boundaries and barriers. It incorporates the entire global world. Through his story, Changez explicitly demonstrates that the US is this new type of Empire. His job as a financial analyst in a valuation company allows him to understand how economic interests define the domestic and international politics. After 9/11 protagonist’s American dream is broken and his world changed. He returns to Pakistan and sees how poor and miserable is his country. Changez constantly compares his disposed native land and prosperous American life. The author of the article compares this narrative segment with the recent interpretation of Jurgen Habermas nowadays Islamic fundamentalism. Habermas states the globalization of markets and expansion of foreign direct investments caused the split of the world into winner and loser countries. In this context, the USA appears as an insult to the self-confidence of the Arab world. This is, according to Habermas, one of the factors that distorted the communicative act between East and West. Changez’s monologue is a vivid illustration of this situation. The identity crisis of the protagonist is resolved during his staying in Valparaiso. There he met the old man who told him about the janissaries. In the end, Changez understands that he is a modern-day janissary. He returns to Lahore and became a university lecturer. His main mission was to advocate a disengagement of Pakistan from the US influence. It is concluded in the article that the successful dialogue between East and West depends on the widening of their original perspectives and a “fusion of horizons” (Habermas). Changez’s monologue is an attempt to introduce the Islamic perspective that has been mostly neglected in the western discourse.